2019
DOI: 10.1088/1752-7163/aaf010
|View full text |Cite
|
Sign up to set email alerts
|

Use of an innovative and non-invasive device for virologic sampling of cough aerosols in patients with community and hospital acquired pneumonia: a pilot study

Abstract: Background: The aetiology of lower respiratory tract infections is challenging to investigate. Despite the wide array of diagnostic tools, invasive techniques, such as bronchoalveolar lavage (BAL), are often required to obtain adequate specimens. PneumoniaCheck TM is a new device that collects aerosol particles from cough, allowing microbiological analyses. Up to now it has been tested only for bacteria detection, but no study has investigated its usefulness for virus identification. Methods: In this pilot stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Various studies conducted during flu seasons have shown the feasibility of detecting viruses in exhaled breath condensates using commercially available bio-samplers and cough sampling systems [9][10][11]. Even face mask sampling-a low-cost method-has also proved to be effective for analyzing exhaled/expelled respiratory particles and detecting respiratory pathogens like the influenza virus [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies conducted during flu seasons have shown the feasibility of detecting viruses in exhaled breath condensates using commercially available bio-samplers and cough sampling systems [9][10][11]. Even face mask sampling-a low-cost method-has also proved to be effective for analyzing exhaled/expelled respiratory particles and detecting respiratory pathogens like the influenza virus [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, contamination with bacteria from the upper airways (Streptococcus mitis) was found in 93% of sputum samples versus 0% in the cough samples suggesting sampling of the lower airways with their device. Patrucco et al investigated the PneumoniaCheck TM in a small cohort of pneumonia patients where they found a good correlation of the results with BAL samples for non-herpes viruses [23].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, up to now only few and no specific data are present in the literature regarding the prevalence of mycotic infections among patients who are hospitalized for suspected SARS-CoV-2 pulmonary infection with pulmonary infiltrates, outside the intensive care unit (ICU). Although in many clinical situations a non-invasive approach can be considered sufficient for the diagnostic work-up [23], some studies have investigated the role of bronchoscopy for diagnosis in COVID-19 patients: most of them confirmed the limited place of BAL in SARS-CoV-2 diagnosis, suggesting a role in resolving diagnostic complex cases [7]. In these studies, mycotic infections represent a relevant part of pathogens isolated on BAL: in the paper of Barberi et al among 166 negative BAL for COVID-19, a mycotic agent was identified 38 times (22.9%), with Aspergillus fumigatus and Candida spp being the most isolated ones [24].…”
Section: Discussionmentioning
confidence: 99%